Pengaruh Pemain Sepakbola Diaspora sebagai Brand Ambassador dan Fanatisme Supporter serta Desain Produk Terhadap Keputusan Pembelian Produk Jersey Tim Nasional Indonesia pada Ultras Garuda Samarinda - Muhammad Zaky Firmansyah; Muhammad Wasil (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the influence of diaspora football players as brand ambassadors, supporter fanaticism, and product design on the purchase decisions of the Indonesian National Team jersey among Ultras Garuda Samarinda. Using a quantitative method with 102 respondents and multiple linear regression analysis, the partial test results show that all three variables have a positive and significant effect, with supporter fanaticism being the most dominant factor. Simultaneously, the three variables significantly affect purchase decisions, with an R² value of 0.781, indicating that 78.1% of the variation in purchase decisions can be explained by the model. These findings emphasize that purchase decisions for the national team jersey are influenced not only by product visual aspects but also by supporters’ emotional attachment and positive perceptions of diaspora players as representations of a modern Indonesian National Team image.